BEBERAPA FAKTOR YANG MEMPENGARUHI PRODUKTIVITAS DAN UPAH TENAGA KERJA PADA INDUSTRI TENUN IKAT DI KECAMATAN BLAHBATUH GIANYAR - Fasanta, Pande Kadek Livia; Karmini, Ni Luh (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2022)
This study aims to determine the effect of working hours and work experience on the productivity and wages of workers in the weaving industry in Blahbatuh District. The sample used was 76 respondents and obtained through purposive sampling method. Research data obtained from the results of distributing questionnaires and interviews with respondents. Data analysis was carried out using path analysis test. The results of the study found that working hours and work experience had a positive and significant effect on labor productivity in the weaving industry, Blahbatuh District, Gianyar. Hours of work, work experience, and productivity have a positive and significant effect on labor wages in the weaving industry in Blahbatuh District, Gianyar. Productivity mediates the effect of working hours on the wages of temporary workers and is not a mediating variable on the effect of work experience on wages in the weaving industry in Blahbatuh Gianyar District. Based on the results of interviews, there are still many workers who are still unable to manage their working time. Because in one day there are those who work 7 hours per day. It is better for the workforce to make their working hours more effective so that each worker is able to optimize their productivity and wages. In addition, the different work experiences of the workforce will also have an impact on the productivity and wages received by the workforce.